2012
DOI: 10.1637/10253-052412-case.1
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak and Source Investigation of Enterococcal Spondylitis in Broilers Caused by Enterococcus cecorum

Abstract: Enterococcus cecorum was isolated from spondylitis lesions in broilers from two flocks in North Carolina that were experiencing increased mortality. Affected birds showed paresis and paralysis, clinical signs characteristic of enterococcal spondylitis (ES). Affected birds rested on their hocks and caudal abdomens with legs extended forward and were unable to stand or walk. Necropsy examination of affected birds revealed firm to hard inflammatory masses involving the vertebral bodies at the level of the free th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 14 publications
6
64
0
1
Order By: Relevance
“…Any immunosuppressive condition would naturally impair the ability to combat an opportunistic infection with E. cecorum, which is a normal intestinal commensal. Differences in pathogenicity between clinical and commensal intestinal isolates have also been proposed (Martin et al 2011;Robbins et al 2012;Stalker et al 2010), with evidence reported by Boerlin et al (2012) suggesting that the emergence of clones is more likely to cause opportunistic infections. It has been observed that the disease can persist in a site from one cycle to the next, implicating the environment as a source for such E. cecorum strains of varying virulence (De Herdt et al 2008;Kense & Landman 2011).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Any immunosuppressive condition would naturally impair the ability to combat an opportunistic infection with E. cecorum, which is a normal intestinal commensal. Differences in pathogenicity between clinical and commensal intestinal isolates have also been proposed (Martin et al 2011;Robbins et al 2012;Stalker et al 2010), with evidence reported by Boerlin et al (2012) suggesting that the emergence of clones is more likely to cause opportunistic infections. It has been observed that the disease can persist in a site from one cycle to the next, implicating the environment as a source for such E. cecorum strains of varying virulence (De Herdt et al 2008;Kense & Landman 2011).…”
Section: Resultsmentioning
confidence: 96%
“…Early detection, differentiation from conditions with similar clinical signs and treatment are important to limit the losses incurred as a result of the disease. The ages of broiler breeders in recorded outbreaks range from 3-18 weeks (Armour et al 2011;De Herdt et al 2008;Robbins et al 2012), an age span that correlates with a period of rapid skeletal development in the birds. The highly vascularised nature of growth plates in rapidly growing bones, in particular, has been reported to leave such articulating bones susceptible to vascular trauma and bacterial infection during the resultant capillary bed expansion (Collett 2013;Wiseman & Prisby 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterococci are involved also as etiological agents of infections in veterinary medicine, such as mastitis in cattle, diarrhea in swine and cattle, as well as endocarditis, septicemia, spondylitis, and amyloid arthropathy in poultry [7,8].…”
Section: Introductionmentioning
confidence: 99%